2020
DOI: 10.1177/1362361320959503
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal problems are associated with increased repetitive behaviors but not social communication difficulties in young children with autism spectrum disorders

Abstract: Individuals with autism spectrum disorder are more likely than typically developing individuals to experience a range of gastrointestinal abnormalities, including chronic diarrhea, constipation, food sensitivities, and abdominal pain. These gastrointestinal symptoms have been associated with higher levels of irritability and aggressive behavior, but less is known about their relationship with core autism spectrum disorder symptoms. We investigated the relationship between autism spectrum disorder and gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…However, the multiple regression model of SRS-2 scores using the three clinical GI variables was not found to be statistically significant, perhaps due to limited sample size.. Abdominal pain significantly contributed to the SRS-2 outcome, thus providing evidence of its strong relationship to severity of social symptoms. This finding is consistent with other studies that have reported relationships between GI symptoms and severity of specific ASD symptoms, including social withdrawal [ 20 , 24 ], anxiety [ 20 , 25 ], repetitive behaviors and stereotypes [ 26 ], expressive language deficits [ 27 ], sleep problems [ 28 ], and sensory sensitivity [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the multiple regression model of SRS-2 scores using the three clinical GI variables was not found to be statistically significant, perhaps due to limited sample size.. Abdominal pain significantly contributed to the SRS-2 outcome, thus providing evidence of its strong relationship to severity of social symptoms. This finding is consistent with other studies that have reported relationships between GI symptoms and severity of specific ASD symptoms, including social withdrawal [ 20 , 24 ], anxiety [ 20 , 25 ], repetitive behaviors and stereotypes [ 26 ], expressive language deficits [ 27 ], sleep problems [ 28 ], and sensory sensitivity [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…For the children with GI symptomatology of abdominal pain and/or atypical stools, greater social and sensory symptom severity was observed. These findings extend understanding of results from other studies that have examined psychological and behavioral impacts of frequent GI symptomatology—specifically, studies reporting strong correlations among GI symptomatology, sociability, and behavioral symptoms in children with ASD (e.g., [ 26 , 31 , 32 ]). These findings are also consistent with those from researchers who have found severely restricted behaviors in ASD, such as rigid and compulsive behaviors, to be associated with functional constipation [ 33 ] and diarrhea [ 34 ].…”
Section: Discussionsupporting
confidence: 81%
“…Unexpectedly, those who did not engage in either SIB or aggression were more likely to experience GI problems such as constipation and diarrhea. Other researchers have reported a relationship between GI issues and challenging behaviors [7,21], whereas Maenner, Arneson, Levy, Kirby, and Nicholas et al [22] reported that aggressive behaviors were common in those both with and without GI problems in a large-scale study of children with ASD.…”
Section: Sib Aggression Sib/aggression Neither Behavior Early Signsmentioning
confidence: 97%
“…As mentioned earlier, ASD is associated with a range of chronic GI symptoms, including altered bowel habits, abdominal pain, and food intolerance [ 37 ]. Gut distress or abdominal discomfort can give rise to behavioral difficulties and potentiate ASD’s core stereotypical behaviors, like mouthing gestures, screaming, and self-injury to the abdomen to relieve pain [ 35 ]. However, because of communicative defects in ASD patients, GI issues often remain undiagnosed and hence untreated.…”
Section: Increasing Prevalence Of Gi Issues In Asd Patients: Evidence For Altered Gut-brain Axismentioning
confidence: 99%